Downregulated Translation Initiation Signaling Predisposes Low-Birth-Weight Neonatal Pigs to Slower Rates of Muscle Protein Synthesis - Chen, Ying; McCauley, Sydney R.; Johnson, Sally E.; Rhoads, Robert P.; El-Kadi, Samer W. (Frontiers in Physiology, 2017)
Low-birth-weight (LBWT) neonates experience restricted muscle growth in their perinatal life. Our aim was to investigate the mechanisms that contribute to slower skeletal muscle growth of LBWT neonatal pigs. Twenty-four 1-d old male LBWT (816±55 g) and normal-birth-weight (NBWT; 1,642±55 g) littermates (n = 12) were euthanized to collect blood and longissimus dorsi (LD) muscle subsamples. Plasma glucose, insulin and insulin-like growth factor-I (IGF-Ι) were lower in LBWT compared with NBWT pigs. Muscle IGF-I mRNA expression were lower in LBWT than NBWT pigs. However, IGF-Ι receptor mRNA and protein abundance was greater in LD of LBWT pigs. Abundance of myostatin and its receptors, and abundance and phosphorylation of smad3 were lower in LBWT LD by comparison with NBWT LD. Abundance of eukaryotic initiation factor (eIF) 4E binding protein 1 and mitogen-activated protein kinase-interacting kinases was lower in muscle of LBWT pigs compared with NBWT siblings, while eIF4E abundance and phosphorylation did not differ between the two groups. Furthermore, phosphorylation of ribosomal protein S6 kinase 1 (S6K1) was less in LBWT muscle, possibly due to lower eIF3e abundance. In addition, abundance and phosphorylation of eIF4G was reduced in LBWT pigs by comparison with NBWT littermates, suggesting translation initiation complex formation is compromised in muscle of LBWT pigs. In conclusion, diminished S6K1 activation and translation initiation signaling are likely the major contributors to impaired muscle growth in LBWT neonatal pigs. The upregulated IGF-I R expression and downregulated myostatin signaling seem to be compensatory responses for the reduction in protein synthesis signaling.